2021
DOI: 10.3390/f12030348
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Characteristics of Photosynthesis and Nitrogen Utilization in Leaves of the Black Locust (Robinia pseudoacacia L.) According to Leaf Position

Abstract: Robinia pseudoacacia L. has been widely planted worldwide for a variety of purposes, but it is a nonindigenous species currently invading the central part of Japanese river terraces. To understand and control this invasion, we investigated how this species invests nitrogen resources in different functions depending on the leaf location, and how these resources are used in physiological reactions such as photosynthesis. The Tama river terrace was examined in Tokyo, Japan. The leaf nitrogen (N) concentration, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…It supports the higher leaf mass per area (LMA) observed in the sun-exposed than in the shaded condition. Sun leaves often have higher LMA than shade leaves, and such a characteristic enhances photosynthetic rates on an area basis (Choi et al 2021). This result suggests that the seedlings are allocating more resources to producing denser and thicker leaves in response to increased light availability.…”
Section: Resultsmentioning
confidence: 97%
“…It supports the higher leaf mass per area (LMA) observed in the sun-exposed than in the shaded condition. Sun leaves often have higher LMA than shade leaves, and such a characteristic enhances photosynthetic rates on an area basis (Choi et al 2021). This result suggests that the seedlings are allocating more resources to producing denser and thicker leaves in response to increased light availability.…”
Section: Resultsmentioning
confidence: 97%
“…The photosynthetic rate was determined with a portable photosynthesis transpiration system (LI‐6400, LiCor, Nebraska, USA) with a blue light LED source (LI‐6400‐02) attached. P sat and gs (stomatal conductance) were determined under steady leaf temperature (25°C), and PPFD was around 1400 μmol m −2 s −1 as previously determined (Choi et al, 2021; Koike et al, 2009). The maximum photosynthetic rate of light and CO 2 saturation ( P max ) was determined at CO 2 1700 μmol mol −1 , PPFD of 1500 μmol m −2 s −1 , and a leaf temperature of 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the photosynthetic rate is positively correlated with N in leaves (Hikosaka, 2010; Larcher, 2003); about 70% of leaf N is allocated to photosynthesis‐related proteins (Evans, 1989). When tree seedlings grow under shady conditions, leaf N is mainly allocated to light‐harvesting proteins on thylakoid membrane (Choi et al, 2021; Kitaoka & Koike, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it may be attributed to the decreased capacity to fix CO 2 by the branch under shaded conditions [59]. Past studies have reported decreased Rubisco and leaf nitrogen content, resulting in reduced CO 2 fixation under shade conditions [60]. The reduction in g s could also be due to a higher ratio of intercellular CO 2 concentration (C i ) to ambient CO 2 concentration (C a ).…”
Section: Effect Of Shade On Water Relationsmentioning
confidence: 99%